2021
DOI: 10.1021/acsomega.1c01342
|View full text |Cite
|
Sign up to set email alerts
|

Toward Reducing Surfactant Adsorption on Clay Minerals by Lignin for Enhanced Oil Recovery Application

Abstract: The significant loss of surfactants during reservoir flooding is a challenge in oil field operations. The presence of clay minerals affects the surfactant performance, resulting in surfactant losses. This is because the mineralogical composition of the reservoir results in unpredicted adsorption quantity. Therefore, this paper seeks to investigate Aerosol-OT’s adsorption on different quartz/clay mineral compositions during the flow. Also, it investigates adsorption mitigation by preflushing with lignin. The dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…This lays the foundation for understanding the critical role the electrical double layer plays in the quest for mineral wettability control. Several mechanisms, including multivalent ionic exchange, electrical double layer (EDL) expansion, electrostatic bond interactions, surface charge alteration, and calcite dissolution, have been proposed in the literature to be responsible for the carbonate rock wettability. This is further highlighted by the report of Al-Bayati et al who described the changes in the carbonate rock samples and concluded that the observed recovery was caused by the electrical double layer effect brought on by the injected fluid’s reduced ionic strength. Our findings further provide evidence to support the conclusions by Al-Bayati et al; however, mineral dissolution as a governing mechanism is ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…This lays the foundation for understanding the critical role the electrical double layer plays in the quest for mineral wettability control. Several mechanisms, including multivalent ionic exchange, electrical double layer (EDL) expansion, electrostatic bond interactions, surface charge alteration, and calcite dissolution, have been proposed in the literature to be responsible for the carbonate rock wettability. This is further highlighted by the report of Al-Bayati et al who described the changes in the carbonate rock samples and concluded that the observed recovery was caused by the electrical double layer effect brought on by the injected fluid’s reduced ionic strength. Our findings further provide evidence to support the conclusions by Al-Bayati et al; however, mineral dissolution as a governing mechanism is ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Multivalent ionic exchange, an EDL expansion, electrostatic bond interactions, surface charge alteration, and calcite dissolution are the wettability modification mechanisms connected with carbonate rocks. , This is highlighted in the report of Al-Bayati et al who described the change in the carbonate rock samples and concluded that the observed recovery was caused by the EDL effect brought on by the injected fluid’s reduced ionic strength. Thus, understanding the electrostatic interaction at the rock surface caused by the salinity and composition of the brine is necessary to understand these mechanisms.…”
Section: Wettability Alteration and The ζ-Potentialmentioning
confidence: 99%
“…In these types of the systems, the polymer adsorption occurs via th polymer-surfactant complexes. [35,36] (3) The most complicated situation occurs when both the polymer and the surfactant adsorb on the surface and additionally interact with each other in the bulk solution. This type of adsorption of two components depends on to their concentrations and properties.…”
Section: Introductionmentioning
confidence: 99%
“…Only one of the components can adsorb on the solid surface, but both adsorbates can interact in the bulk solution. In these types of the systems, the polymer adsorption occurs via th polymer‐surfactant complexes [35,36] The most complicated situation occurs when both the polymer and the surfactant adsorb on the surface and additionally interact with each other in the bulk solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation